Compliance In The Implementation Of Hand Hygiene Activities By Nurses At Siti Khodijah Muhammadiyah Hospital, Sepanjang Branch–Sidoarjo - Ida Agustiningsih; Siswanto Agung Wijaya (International Journal of Scientific Multidisciplinary Research, 2023)
Compliance with hand hygiene activities is an important aspect in maintaining patient health, preventing the spread of nosocomial infections, and improving nursing clinical practice standards. This study aims to analyze the level of compliance with the implementation of hand hygiene activities by nurses in several inpatient service units. This research method uses a quantitative descriptive approach involving a sample of nurses from several inpatient rooms. Data was collected through direct observation of the practice of 5 moments of hand hygiene as well as a questionnaire regarding compliance procedures for implementing hand hygiene activities. The results of the study showed that the level of compliance with the implementation of the 5 moments hand hygiene activities among inpatient room nurses was 94% for the moments before carrying out aseptic procedures, with almost all service units achieving a high level of compliance. Meanwhile, the moment before contact with the patient was 87%. Factors that influence compliance include knowledge, attitudes, accessibility of hand hygiene facilities, available time, and organizational culture. This research provides deeper insight into the obstacles faced by nurses in maintaining compliance with the implementation of hand hygiene activities. The results of this research can be used as a basis for developing interventions aimed at increasing and maintaining compliance with the implementation of hand hygiene activities, including training, supervision and facility improvements